2003
DOI: 10.1128/jvi.77.12.7026-7033.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Nuclear Localization Signal for a Suppressor of Posttranscriptional Gene Silencing

Abstract: The nucleus-localized C2 protein of Tomato yellow leaf curl virus-China (TYLCV-C) is an active suppressor of posttranscriptional gene silencing (PTGS). Consistently, infection with TYLCV-C resulted in PTGS arrest in plants. The C2 protein possesses a functional, arginine-rich nuclear localization signal within the basic amino acid-rich region 17 KVQHRIAKKTTRRRR 31 . When expressed from potato virus X, C2-RRRR 31 DVGG (in which the four consecutive arginine residues 28 RRRR 31 were replaced with DVGG) that had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 49 publications
3
72
0
1
Order By: Relevance
“…Studies on AC2 of African cassava mosaic virus (ACMV) and the homologous C2 of Tomato yellow leaf curl virus-China (TYLCCNV), a related monopartite begomovirus, have implicated these proteins in suppression of RNA silencing (10,17,50,53). Notably, TYLCCN C2 requires functional NLS and Zn-finger domains to suppress silencing (10,50). In this work, we found that AC2 from MYMV serves as a transactivator of viral promoter and as a suppressor of RNA silencing.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Studies on AC2 of African cassava mosaic virus (ACMV) and the homologous C2 of Tomato yellow leaf curl virus-China (TYLCCNV), a related monopartite begomovirus, have implicated these proteins in suppression of RNA silencing (10,17,50,53). Notably, TYLCCN C2 requires functional NLS and Zn-finger domains to suppress silencing (10,50). In this work, we found that AC2 from MYMV serves as a transactivator of viral promoter and as a suppressor of RNA silencing.…”
mentioning
confidence: 78%
“…The latter suggests that the KKR motif (mutated in NLS1 Ϫ ) is an essential part of the AC2 NLS. However, in the C2 protein of TYLCCNV, the corresponding KKT26DIT mutation did not abolish nuclear localization, in contrast to mutation RRRR31DVGG in the neighboring motif (10). We therefore also mutated the corresponding motif in the MYMV AC2 (RRSR31AASA [NLS2-]).…”
Section: Ac2 Transactivates Viral Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…In Caenorhabditis elegans, nuclear proteins are reportedly required for RNAi (Dudley et al 2002). It has also been suggested that 21-to 22-nt siRNAs are produced in the nucleus of plants by a nuclear Dicer-like protein (Papp et al 2003), and that PTGS can occur in the nucleus of plants (Dong et al 2003;Papp et al 2003). Additionally, siRNAmediated degradation of the nuclear-localized 7SK RNA (Robb et al 2005) and DMPK mRNA (Langlois et al 2005) has been shown to occur in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…In general, viruses accomplish counter-defense by targeting RNAs (Guo and Ding 2002;Thomas et al 2003;Qu et al 2003) or protein (Anandalakshmi et al 2000). Therefore, expression of host genes is modified or silenced (Dong et al 2003). Recent findings suggest that silencing suppressors can contribute to viral symptoms in two ways: helping virus accumulation indirectly and modifying endogenous short-RNA-regulated pathways directly (Silhavy and Burgyán 2004).…”
Section: Roles Of Mirnas In Plant-virus Armament Competitionmentioning
confidence: 99%